Pengaruh Kompensasi dan Pengembangan Karir Terhadap Kepuasan Kerja (Studi Pada Karyawan Departemen PPIC PT. Shoetown Ligung Indonesia) - R. Neny Kusumadewi; L Suparto; Alan Rusdiana; Tino Foezi Hadi Suarno (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Human resources are an important element in an organization, especially forbusiness organizations. Therefore, many companies are starting to seriouslybuild and develop their human resources. Considering the importance of humanresources in an organization, companies must pay attention to employeesatisfaction. Job satisfaction is also related to outcomes such as performance, sothat if job satisfaction is higher it will create enthusiasm for work.The aim of this research is to identify the influence of compensation and careerdevelopment on job satisfaction. The population in this study were employees ofthe PPIC department of PT. Shoetown Ligung Indonesia, numbering 305 people.The research sample consisted of 100 people taken using purposive samplingtechnique. The data analysis method is multiple linear regression analysis usingSPSS 26.The results of this research state that compensation and career development havea positive and significant effect on job satisfaction, both partially andsimultaneously